Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve for [tex]\((11 + 4i)(2 - 5i)\)[/tex], let's follow these steps:
1. Distribute each term in the first binomial by each term in the second binomial:
[tex]\[ (11 + 4i)(2 - 5i) = 11 \cdot 2 + 11 \cdot (-5i) + 4i \cdot 2 + 4i \cdot (-5i) \][/tex]
2. Compute each of these products:
[tex]\[ 11 \cdot 2 = 22 \][/tex]
[tex]\[ 11 \cdot (-5i) = -55i \][/tex]
[tex]\[ 4i \cdot 2 = 8i \][/tex]
[tex]\[ 4i \cdot (-5i) = -20i^2 \][/tex]
3. Simplify the product of imaginary units [tex]\(i^2\)[/tex]:
Since [tex]\(i^2 = -1\)[/tex], we have:
[tex]\[ -20i^2 = -20(-1) = 20 \][/tex]
4. Add up all the terms, combining like terms:
[tex]\[ 22 + (-55i) + 8i + 20 \][/tex]
5. Combine the real and imaginary parts separately:
The real parts:
[tex]\[ 22 + 20 = 42 \][/tex]
The imaginary parts:
[tex]\[ -55i + 8i = -47i \][/tex]
Therefore, the expression [tex]\((11 + 4i)(2 - 5i)\)[/tex] simplifies to:
[tex]\[ 42 - 47i \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{42 - 47i} \][/tex]
From the given options, the correct match is:
[tex]\[ \boxed{E} \][/tex]
1. Distribute each term in the first binomial by each term in the second binomial:
[tex]\[ (11 + 4i)(2 - 5i) = 11 \cdot 2 + 11 \cdot (-5i) + 4i \cdot 2 + 4i \cdot (-5i) \][/tex]
2. Compute each of these products:
[tex]\[ 11 \cdot 2 = 22 \][/tex]
[tex]\[ 11 \cdot (-5i) = -55i \][/tex]
[tex]\[ 4i \cdot 2 = 8i \][/tex]
[tex]\[ 4i \cdot (-5i) = -20i^2 \][/tex]
3. Simplify the product of imaginary units [tex]\(i^2\)[/tex]:
Since [tex]\(i^2 = -1\)[/tex], we have:
[tex]\[ -20i^2 = -20(-1) = 20 \][/tex]
4. Add up all the terms, combining like terms:
[tex]\[ 22 + (-55i) + 8i + 20 \][/tex]
5. Combine the real and imaginary parts separately:
The real parts:
[tex]\[ 22 + 20 = 42 \][/tex]
The imaginary parts:
[tex]\[ -55i + 8i = -47i \][/tex]
Therefore, the expression [tex]\((11 + 4i)(2 - 5i)\)[/tex] simplifies to:
[tex]\[ 42 - 47i \][/tex]
Thus, the correct answer is:
[tex]\[ \boxed{42 - 47i} \][/tex]
From the given options, the correct match is:
[tex]\[ \boxed{E} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.